Teacher motivation in the context of school physical education (Research, Society and Development, 2020)
Introduction: Motivation, according to the Theory of Self-Determination, is presented in three levels: extrinsic motivation, intrinsic motivation and demotivation. Objective: The study aimed to verify and tounderstand, from the teachers' perception, what are the factors that could in fluence the motivation of physical education professionals in the school context. Methodology: The qualitative methodology of the exploratory and descriptive type wasused. We interviewed 12 high school teachers from public and private schools in Santo André and São Caetano do Sul cities. The research was conducted through a questionnaire, developed for this study, containing 10 open questions. The form of analys is of the results was through the technique called Content Analysis. Result: The most expressive results stood out the salary, as it represented about 29.64% of the factors considered more influential (extrinsic motivation). Conclusion: The develop ment of the present study made it possible to verify which factors can influence the motivation of the high school physical education teacher and, in fact, to think of actions for possible modifications. The extrinsic factors were the most influential in motivation and among them, represented hierarchically, salary, school management and work routine were considered the most relevant for professional motivation, while intrinsic factors such as love for the profession and the teacher's relationship with his/her work should also be considered relevant.